Improving Basic Movement Skills of Pencak Silat Empty-Hand Moves for Students with Physical Disabilities through Peer Teaching at Elementary School 1 Giritirto Karanggayam - Burhaein, Erick; Alfaridzi, Afandi; Demirci, Nevzat (Universitas Negeri Yogyakarta, 2025)
The purpose of this study is to improve basic unarmed pencak silat skills in students with physical disabilities through a peer tutor approach at SD Negeri 1 Giritirto Karanggayam. This study aims to develop an adaptive learning model to increase student participation in physical activities and support an inclusive school environment (Fernández-Batanero et al., 2024). The research subject was a 10-year-old fifth-grade student. The method used was classroom action research (CAR) with two cycles, including planning, action, observation, and reflection stages. The results showed an increase in ability from 53% before the action to 66% in cycle I and 80% in cycle II, exceeding the success criterion of 75%. The peer tutor approach proved effective in improving the striking, kicking, and basic movement coordination skills of students with physical disabilities in pencak silat, as well as fostering self-confidence, motivation, empathy, and social awareness among students and physical education teachers. Further research is recommended to test the effectiveness of this method on other types of disabilities and compare it with other inclusive learning approaches.